THE INFLUENCE OF TOURIST & WOM'S EMOTION ON DESTINATION IMAGE AND THE IMPACT ON THE DESIRE TO REVISIT WISATA MENARA KUDUS - Septanti, Annisya Lutfi; Anggun, Anggraini; Putri, Widyadhana Nadia; Himayani, Faza Aurellia; Lusianti, Dina (ITB AAS Indonesia Surakarta, 2024)
One of the most significant industries supporting a nation's economy is the tourist sector. Religious tourism is one type of travel that has a big financial influence on the neighborhood. The increasing number of visitors and their intention to return to the tourist destination are indicators of the industry's success. For instance, there has been a noticeable annual growth in the number of tourists visiting Central Java. The Kudus Regency, also referred to as the cities of Santri and Kretek, is located in the Central Java Province. Menara Kudus religious tourism is one among the tourist attractions in Kudus Regency. In contrast to the Colo Tourist Attraction in 2021, the Menara Kudus Tour is currently seeing a decline in visitors. The purpose of this study is to ascertain how WOM and Tourist Emotion affect Menara Kudus' destination image and how much it influences travelers' intentions to return. This study employs a quantitative methodology and surveys Menara Kudus tourists with a questionnaire. The tool or method Smart-PLS 3.0 was used to evaluate the data. Purposive sampling was utilized to choose the sample for this study, which included 132 respondents who visited Menara Kudus. According to the research's findings, (1) Tourist Emotions have a positive impact on destination image; (2) word-of-mouth (WOM) has a positive impact on destination image; (3) Tourist Emotions do not have a positive or significant impact on the Revisit Intention; (4) WOM has a positive impact on the Revisit Intention; and (5) destination image has a positive impact on the Revisit Intention.